An Atypical Femoral Fracture in a Patient on Long-term Alendronate Therapy. Issue 3 (September 2014) - Celbek, Gokhan; Ozsahin, Mustafa; Uslu, Mustafa; Onder, Elif; Kutlucan, Ali; Besir, Fahri Halit; Aydin, Yusuf
Abstract Background: Biphosphonates, especially alendronate, are used extensively and successfully for the treatment of osteoporosis. However, there are numerous recent studies that indicate low-energy subtrochanteric femoral fractures can be associated with long-term alendronate therapy. Findings: We present a 76-year-old female patient who has taken 70 mg alendronate per week for 7 years, and who presented with pain in the left thigh. Conclusions: The patient was diagnosed as atypical femoral fracture resulting from long-term alendronate use. The diagnosis and the treatment will be discussed with a review of the literature.